Efficacy and Safety of Nebulized Sodium Bicarbonate in Adults with COVID-19 (SODIC): A Randomized, Single-Center, Double-Blinded, Controlled Trial - Mohammad Khairy El-Badrawy, MD; Rehab Ahmad Elmorsey, MD; Mahmoud Mostafa Elhosiny, MD; Mohammed Shehta, MD; Tamer Ali El-Hadidy, MD; Ibrahim El-Said Abdelwahab, MD; Adel El-Badrawy, MD; Ahmed A. Shokeir, MD (Current Therapeutic Research, 2025)
Background: Entry of severe acute respiratory syndrome coronavirus 2 into a host cell is pH-dependent. Hence, intracellular alkalinization by nebulized sodium bicarbonate could elevate endosomal pH and then block viral entry into the host cells. Objective: To study the efficacy of nebulized sodium bicarbonate as an adjuvant treatment for coronavirus disease 2019 (COVID-19). Methods: A prospective, randomized, double-blinded trial was conducted in Mansoura University Hospital, Egypt. Eligible patients were >18 years old with all COVID-19 severities. Patients were electronically randomly assigned (1:1) to receive standard treatment only (control group) (274 patients) or standard treatment plus nebulized sodium bicarbonate (272 patients). The primary end points were time to clinical improvement, defined as number of days from diagnosis until reporting of a better feeling by the patients; length of hospital stay for admitted patients; and mortality. This study was registered at ClinicalTrials.gov (NCT05035524) on September 2, 2021, and has been completed. Results: Between September 2, 2021, and April 30, 2022, 546 patients (215 men and 331 women) were enrolled and randomly allocated for treatment. Mean (SD) age was 50.7 (16.8) years. Study showed a significantly shorter time to clinical improvement and length of hospital stay in the study group (P < 0.001), and the number of deaths was significantly low only in the severe grade of the study group (11 cases in the study group vs 22 cases in the control group, P = 0.014). C-reactive protein and D-dimer levels measured at 1 week were significantly lower in the severe cases of the study group (P = 0.001). The overall median computed tomography score was significantly better in the study group at all points of follow-up (P < 0.05). All patients reported mild irritative cough initially with sodium bicarbonate inhalation. No serious treatment adverse events were observed. Conclusions: Nebulized sodium bicarbonate (8.4%) could be a possible adjuvant therapy for patients with moderate and severe COVID‑19. ClinicalTrials.gov identifier: NCT05035524.